Coral Fishes Community On The Artificial Coral Reefs Of Kareko Waters, North Lembeh Island District, Bitung City, North Sulawesi - Awuy, Gisela; Rondonuwu, Ari B.; Kambey, Alex Denny (Jurnal Ilmiah Platax, 2017)
The aim of this research is to determine the species richness, individual abundance, and the ecology index of the coral fishes on the artificial reef of Kareko waters,Â  District of North Lembeh - Bitung City. The data is collected using â€œVisual Censusâ€ technique by scuba diving. The amount of the reef fishes found in the artificial coral reefs were 53 species. The abundance species in the artificial reefs which made from metal were 34 species and which made from concrete were 35 species. The total of number individuals of coral fishes from 47 species is 210.50 individuals/30m2. The total density was 7,017 individuals/m2. The highest relative density on iron-made reefs was found in Dascyllus trimaculatus (15.73%) and and which made from concrete were Dascyllus reticulatus (10.85%).Â  Based on Hâ€™, Hâ€™max, and Hâ€™min, the diversity IndexÂ  of coral fishes in both artificial reefs including high.Keywords : Coral Fishes, Artificial Reef, KarekoÂ ABSTRAKTujuan penelitian ini yaitu untuk mengetahui kekayaan spesies, kelimpahan individu, dan indeks ekologi ikan karang pada terumbu buatan di Perairan Kareko. Kecamatan Lembeh Utara, Kota Bitung. Pengambilan data dilakukan dengan menggunakan teknik â€œSensus Visualâ€ dengan melakukan penyelaman SCUBA. Jumlah spesies ikan karang yang ditemukan pada terumbu buatan yaitu 53 spesies. Kekayaan spesies di terumbu buatan yang terbuat dari besi berjumlah 34 spesies, sedangkan di terumbu buatan beton berjumlah 35 spesies. Kelimpahan individu total ikan karang dari 47 spesies yaitu 210,50 individu/30 m2 sedangkan kepadatan/densitas total adalah 7,017 individu/m2. Kepadatan relative tertinggi untuk terumbu buatan besi ditemukan pada jenis Dascyllus trimaculatus (15,73%) dan untuk terumbu buatan beton ditemukan pada jenis Dascyllus reticulatus (10,85%). Berdasarkan nilai Hâ€™, Hâ€™max, and Hâ€™min, indeks keanekeragaman ikan karang pada kedua jenis terumbu buatan tergolong tinggi.Keywords : Coral Fishes, Artificial Reef, Kareko